JIHAD DAN TERORISME KAJIAN FIKIH KONTEMPORER - Mathar, M. Saleh (Hunafa: Jurnal Studia Islamika, 2009)
This article discusses jihâd and terrorism based on contemporary fiqh perspective. Jihâd has an important meaning in Islamic teaching as a part of religious obligation. However, nowadays the word jihâd has been associated with the term terrorism by Western World. In fact, terrorism is completely different from Islamic spirit (jihâd). Therefore, this article tries to reveal the differences between jihâd and terrorism. This issue is discussed by employing contemporary fiqh perspective approach. The result shows that jihâd and terrorism are totally different from each other. Jihâd has the criteria which are stated in Islamic shar’iah, while terrorism is a form of movement against the Islamic teaching.Kata Kunci: jihad, terorisme, syariah, sadd  al-tharâ’i